Hungary : Financial System Stability Assessment Follow-up, including Reports on the Observance of Standards and Codes on the following topics; Monetary and Financial Policy Transparency, Banking Supervision, Securities Regulation, Insurance Regulation, and Payment Systems. (IMF Staff Country Reports; Country Report, 2002)
This paper presents key findings of the Financial System Stability Assessment Follow-up for Hungary, including Reports on the Observance of Standards and Codes on Monetary and Financial Policy Transparency, Banking Supervision, Securities Regulation, Insurance Regulation, and Payment Systems. The assessment reveals that Hungary is in the final stages of transition to a market economy and has one of the most developed and diversified financial systems in Central and Eastern Europe. The banking system is well managed and capitalized, and the quality of its assets is high.